Contribution of E-Book Implementation to Learning Achievement in Informatics Courses in Antartika - Muhammad Afifuddin Al Islami; Rahmania Sri Untari; Fitria Nur Hasanah; Dicka Y Kardono (Graduate School of Universitas Negeri Malang, 2023)
This study aimed to determine (1) the contribution of E-Books to Informatics class X RPL subject to student achievement at SMK Antarctica 1 Sidoarjo (2) How significant is the contribution to student achievement in Informatics class X RPL at SMK Antarctica 1 Sidoarjo after using the E-Book. This research uses a quantitative method with the type of pre-experimental design one research group pretest-posttest design to compare the results obtained from the pretest and posttest. The population used was 36 students, and the sample was taken using a saturated sampling technique, meaning that all population members were taken to be tested. The data analysis used was descriptive statistical analysis. Based on the results obtained from the implementation of the E-Book in class X RPL 1 SMK Antartika 1 Sidoarjo, it can be concluded that there is a significant contribution to students by increasing student achievement.